2000
DOI: 10.21273/hortsci.35.3.492e
|View full text |Cite
|
Sign up to set email alerts
|

562 Incorporating Zeolite into Soilless Container Media Reduces Nutrient Leaching in Ornamental Plant Production

Abstract: Containerized ornamental plant production represents extremely intensive agricultural production. An average of 200,000 containers may occupy 1 acre of surface area, to which a large amount of chemical fertilizers will be applied. Because of the use of high-drainage soilless potting mixes coupled with excessive fertigation, a great amount of nutrients, particularly nitrogen and phosphorus, are leached, which increases the potential for ground and surface water contamination. Over the past 2 decades, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This provides for initially high concentrations of nutrients needed for young transplants, but if the ''imperfectly coated'' amounts are excessive, it could cause too much leaching early in production (Huett, 1997;Million et al, 2007a), even during initial watering in of transplants (Million et al, 2007b). In this regard, some studies have shown that zeolites, gels, and other active compounds can be used as substrate amendments to retain soluble nutrients such as NO 3 -N and orthophosphorus within the container (Broschat, 2001;Chen et al, 2000). Successful research in this area, particularly in regard to NO 3 -N retention, could help buffer against rapid loss of nutrients under these circumstances.…”
Section: Fertilizer Challenges and Best Management Practicesmentioning
confidence: 99%
“…This provides for initially high concentrations of nutrients needed for young transplants, but if the ''imperfectly coated'' amounts are excessive, it could cause too much leaching early in production (Huett, 1997;Million et al, 2007a), even during initial watering in of transplants (Million et al, 2007b). In this regard, some studies have shown that zeolites, gels, and other active compounds can be used as substrate amendments to retain soluble nutrients such as NO 3 -N and orthophosphorus within the container (Broschat, 2001;Chen et al, 2000). Successful research in this area, particularly in regard to NO 3 -N retention, could help buffer against rapid loss of nutrients under these circumstances.…”
Section: Fertilizer Challenges and Best Management Practicesmentioning
confidence: 99%
“…A solution containing a WSF with N at a concentration of 200 mg/L was applied at 100 mL per pot weekly. Results demonstrated that zeolite-amended media leached 30 to 90% less ammonium depending on zeolite species and up to 50% less nitrate than the control media three months after transplanting ( Table 2) [22]. Zeolite amended media had no adverse effects on plant growth, but rather promoted plant growth compared to control media [23].…”
Section: Improving Container Mediamentioning
confidence: 99%